Accenting the classics editing European music in France, 1915-1925 - Mawer, Deborah 1961-; Kelly, Barbara ca. 20./21. Jh; Moore, Rachel 1981-; Sadler, Graham ca. 20./21. Jh (The Boydell Press, an imprint of Boydell & Brewer Ltd, 2023)
Brings new insights to the music of well-known European composers by telling a fascinating, little-known story about French music publishing, specifically through the lens of Jacques Durand's Édition Classique